ИНФОРМАЦИОННОЕ СОТРУДНИЧЕСТВО ТЮРКОЯЗЫЧНЫХ СТРАН В УСЛОВИЯХ ИНТЕГРАЦИИ (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The article examines the role and significance of information cooperation among Turkic-speaking countries within the broader context of global integration. It provides a comprehensive analysis of the mechanisms, challenges, and future prospects of collaboration in the fields of media, digital communication, and cultural exchange. The study explores how joint initiatives, including media partnerships, digital infrastructure development, and cultural programs, foster deeper regional ties. The findings suggest that strengthened information links contribute to economic growth by facilitating trade and investment, enhance political cooperation by fostering diplomatic dialogue, and promote social stability by improving mutual understanding and preserving cultural identity. Strengthening such cooperation allows Turkic-speaking countries to collectively address global challenges and participate more effectively in international affairs.